1978
DOI: 10.7326/0003-4819-88-6-790
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Antibody Responses After Influenza Immunization in Systemic Lupus Erythematosus

Abstract: After immunization with A/New Jersey/76 and A/Victoria/75 influenza vaccines, 11 patients with systemic lupud erythematosus were serially evaluated for changes in disease activity, serologic abnormalities, and their capability to generate specific antibodies. One patient, with active disease, developed a diffuse, proliferative glomerulonephritis. None of the other patients or control subjects had significant local or systemic side effects. Significant levels of antibodies were generated to A/New Jersey/76 in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
7

Year Published

1979
1979
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 12 publications
3
51
0
7
Order By: Relevance
“…Previous studies of SLE antibody response to immunization have been conflicting. SLE patients showed normal responses to immunization with influenza (22)(23)(24), TT (1), Brucella and Rickettsia (25), and had normal levels of antibodies to AB blood group antigens and Proteus OX-2 (26). In other studies, decreased SLE antibody responses were found upon immunization with influenza (27) and Brucella (28).…”
Section: Methods Cell Isolations Peripheral Blood Mononuclear Cells mentioning
confidence: 81%
“…Previous studies of SLE antibody response to immunization have been conflicting. SLE patients showed normal responses to immunization with influenza (22)(23)(24), TT (1), Brucella and Rickettsia (25), and had normal levels of antibodies to AB blood group antigens and Proteus OX-2 (26). In other studies, decreased SLE antibody responses were found upon immunization with influenza (27) and Brucella (28).…”
Section: Methods Cell Isolations Peripheral Blood Mononuclear Cells mentioning
confidence: 81%
“…Other papers reported a modest reduction or a similar humoral response in SLE patients, but compared to the healthy control group (Brodman et al 1978;Mercado et al 2004;Holvast et al 2006). In several controlled studies in SLE patients a similar humoral response was established after influenza immunization compared to the healthy control group and immunosuppressive therapy has no significant effect on the response to vaccination (Louie et al 1978;Lu et al 2011). On the other hand, there are reports indicating a decreased humoral response in SLE patients treated with immunosuppressive therapy (Abu-Shakra et al 2002;Wiesik-Szewczyk 2010).…”
Section: Discussionmentioning
confidence: 97%
“…В конце 70-х годов прошлого века в США в рамках Национальной программы по вакцинации против гриппа было выполнено пять аналогичных по дизайну исследова-ний [14][15][16][17][18], имевших целью изучить эффективность и пе-реносимость моно-и бивалентной противогриппозных вакцин у больных СКВ в неактивной фазе заболевания. В абсолютном большинстве случаев продемонстрирована высокая иммуногенность вакцины, показатели серокон-версии 1 были аналогичны таковым в контрольной группе.…”
Section: гриппunclassified
“…Через 12 мес после вакцинации показатели сероконверсии по отноше-нию к наиболее значимым HPV-серотипам (6,11,16,18) в исследуемой и контрольной группах составили 82; 89; 95; 76 и 98; 98; 98; 80 соответственно. Лечение преднизолоном и микофенолата мофетилом ассоциировалось с более низ-ким иммунным ответом на вакцину.…”
Section: вирус папилломы человекаunclassified